Causes of Clonal Hematopoiesis: a Review - Joo, LiJin; Bradley, Catherine C.; Lin, Steven H.; Scheet, Paul A.; Nead, Kevin T. (Current oncology reports, 2023)
Purpose of Review Clonal hematopoiesis (CH) is an age-dependent process detectable using advanced sequencing technologies and is associated with multiple adverse health outcomes including cardiovascular disease and cancer. The purpose of this review is to summarize known causes of CH mutations and to identify key areas and considerations for future research on CH. Recent Findings Studies have identified multiple potential causes of CH mutations including smoking, cancer therapies, cardiometabolic disease, inflammation, and germline risk factors. Additionally, large-scale studies have facilitated the identification of gene-specific effects of CH mutation risk factors that may have unique downstream health implications. For example, cancer therapies and sources of environmental radiation appear to cause CH through their impact on DNA damage repair genes. Summary There is a growing body of evidence defining risk factors for CH mutations. Standardization in the identification of CH mutations may have important implications for future research. Additional studies in underrepresented populations and their diverse environmental exposures are needed to facilitate broad public health impact of the study of CH mutations.